1997
DOI: 10.1038/sj.bjp.0700917
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological classification of α1‐adrenoceptors mediating contractions of rabbit isolated ear artery: comparison with rat isolated thoracic aorta

Abstract: 1 The present study attempted to classify pharmacologically the a 1 -adrenoceptor subtype(s) present in two isolated, vascular ring preparations, the rabbit ear artery and rat thoracic aorta. 2 In the ear artery, the agonist e ects of phenylephrine were antagonized by 5-methyl urapidil (pA 2 =7.90; Schild slope=0.85) and BMY 7378 (pA 2 =6.11; Schild slope=0.80) but not in a simple competitive manner. The shallow Schild slopes are consistent with the activation of a heterogeneous receptor population. Indeed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
2
29
2
Order By: Relevance
“…The potencies of tamsulosin and Rec 15/2739 were similar to values obtained in the rabbit urethra (Auguet et al 1995;Leonardi et al 1997), heart (Yang and Endoh 1996), prostate and ear artery (Leonardi et al 1997). Agonist-induced contractions are presumably mediated via α 1L -adrenoceptors in the urethra and prostate (Auguet et al 1995;Leonardi et al 1997) while α 1A -adrenoceptors mediated contractions in the heart (Yang and Endoh 1996) and ear artery (Fagura et al 1997). These results therefore showed that the low antagonist potencies reported for prazosin, WB 4101 and 5-methylurapidil did not arise from methodological artifacts.…”
Section: Discussionsupporting
confidence: 48%
“…The potencies of tamsulosin and Rec 15/2739 were similar to values obtained in the rabbit urethra (Auguet et al 1995;Leonardi et al 1997), heart (Yang and Endoh 1996), prostate and ear artery (Leonardi et al 1997). Agonist-induced contractions are presumably mediated via α 1L -adrenoceptors in the urethra and prostate (Auguet et al 1995;Leonardi et al 1997) while α 1A -adrenoceptors mediated contractions in the heart (Yang and Endoh 1996) and ear artery (Fagura et al 1997). These results therefore showed that the low antagonist potencies reported for prazosin, WB 4101 and 5-methylurapidil did not arise from methodological artifacts.…”
Section: Discussionsupporting
confidence: 48%
“…High pA 2 or pK B values for prazosin and tamsulosin but low affinity for KMD-3213, 5-methylurapidil, RS-17053, and BMY 7378 prove an involvement of ␣-1B AR subtype. Low affinity (pK B : 7.9 and 7.2) for 5-methylurapidil has also been reported in the contractile responses to phenylephrine and noradrenaline of rabbit ear artery (Fagura et al, 1997;Testa et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Since · 2 -adrenoceptors may be involved in contractions of rat aorta, Fujimoto and Itoh [17] pointed out that the · 2 -adrenoceptor agonist clonidine in the thoracic aorta produces contractile activity. But in some studies, clonidine was described as being able to activate the · 1 -adrenoceptor to contract blood vessels [43]. However, the possibility that the rat aorta contains a heterogeneous population of ·-adrenoceptors should not be excluded [17].…”
Section: Discussionmentioning
confidence: 99%